Gender Differentiation in Tryptophan Metabolism in Postmortem Cases - Somlada Watcharakhom; Kanicnan Intui; Yutti Amornlertwatana; Churdsak Jaikang (Institute of Medico-legal Publications Pvt Ltd, 2021)
Tryptophan (TRP) is an essential amino acid and is metabolized via kynurenine and serotonin pathway. Both pathways are significant role in many diseases and have been studied as biomarkers for differentiate and clarify in many diseases including forensic works. Metabolism in the body might be affected by both intrinsic and extrinsic factors. This study aimed to compare postmortem blood level of TRP and its metabolites in male and female to be applied in gender identification in forensic medicine cases. Blood samples were collected from male group (n=11) and female group (n=11) and the level of the TRP and its metabolites were identified by HPLC-DAD. The values of the TRP, metabolites and metabolite ratios did not different between the groups. While, the value of ratio of picolinic acid/ quinolinic acid different significantly (p <0.05) among the groups which might be applied for gender identification in postmortem cases. In conclusion, we found that gender have no effect on the TRP and its metabolites. By the way, the effect of gender should be expanded sample size and develop to gender identification method.